Influence of ultrasonic impact treatment on stress corrosion of 7075 aluminum alloy and its welded joints. (February 2023) - Wang, J.T.; Chen, J.W.; Zhang, Y.K.; Xu, X.L.; Wang, Z.G.; Xie, L.; He, M.T.; Lu, Y.L.; Luo, K.Y.; Wang, M.Z.
Highlights: UIT can increase the hardness of BM by 27.34 % and the welded joints by 25.16 % and induce the compressive stress with the depth of about 50–75 µm. After UITed, the stress corrosion resistance is greatly improved exhibiting the SCC factors I σ, I δ, and SSI decreased dramatically by 37%, 68%, and 46%, respectively. In the three stages including of pit corrosion crack, SCC, and crack fast propagation, the mechanism of stress corrosion is mainly grain refinement and residual compressive stress. Abstract: The effects of ultrasonic impact treatment (UIT) on stress corrosion cracking (SCC) of 7075 aluminum alloy and its welded joints have been investigated. The microstructural evolution, corrosion behavior, and mechanical properties of the UITed and untreated specimens were studied. The results showed that UIT can refine the grains dramatically and induce a compressive residual stress layer with a depth of 50–75 µm on the material surface. The corrosion resistance was also improved, exhibiting that the SCC factors I σ, I δ, and SSI of the specimens with double-side treatments decreased by 37 %, 68 %, and 46 %, respectively. The improved SCC resistance of 7075 aluminum alloy and its welded joints subjected to UIT was mainly attributed to the residual compressive stress and grain refinement, which not only enhanced the pitting corrosion resistance but also effectively inhibited the initiation and growth of corrosion cracking.